Comparing ERAS-outpatient versus standard-inpatient hip and knee replacements: a mixed methods study exploring the experience of patients who underwent both - Alexandre Hardy (BMC, 2021)
Abstract Background Optimizing patients’ total hip and knee arthroplasty (THA/TKA) experience is as crucial for providing high quality care as improving safety and clinical effectiveness. Yet, little evidence is available on patient experience in standard-inpatient and enhanced recovery after surgery (ERAS)-outpatient programs. Therefore, this study aimed to gain a more in-depth understanding of the patient experience of ERAS-outpatient programs in comparison to standard-inpatient programs. Methods We conducted a convergent mixed methods study of 48 consecutive patients who experienced both standard-inpatient and ERAS-outpatient THA/TKA contralaterally. A reflective thematic analysis was conducted based on data collected via a questionnaire. Bivariate correlations between the patient experience and patients’ characteristics, clinical outcomes and care components satisfaction were performed. Then, the quantitative and qualitative data were integrated together. Results The theme Support makes the difference for better and for worse was identified by patients as crucial to their experience in both joint replacement programs. On the other hand, patients identified 3 themes distinguishing their ERAS-outpatient from their standard-inpatient experience: 1) Minimizing inconvenience, 2) Home sweet home and 3) Returning to normal function and activities. Potential optimization expressed by patients were to receive more preoperative information, additional postoperative rehabilitation sessions, and ensuring better coherence of care between hospital and home care teams. Weak to moderate positive and statistically significant correlations were found between patients’ THA/TKA experience and satisfaction with pain management, hospital stay, postoperative recovery, home care, and overall results (rs = + [0.36–0.66], p-value < 0.01). Conclusion Whatever the perioperative program, the key to improving patients’ THA/TKA experience lies in improving support throughout the care episode. However, compared to standard-inpatient care, the ERAS-outpatient program improves patients’ experience by providing dedicated support in postoperative care, reducing postoperative inconvenience, optimizing pain management, returning home sooner, and recovering and regaining function sooner. Patients’ THA/TKA experience could further be enhanced by optimizing the information provided to the patient, the rehabilitation program and the coherence between care teams.